Analyzing temporary overvoltage by the non-islanding operation of distributed generation in multi-grounded neutral distribution system - Yun, Sangwon; Jung, Jaesung (International Journal of Electrical Power and Energy Systems, 2022)
Effective grounding has been applied to mitigate the temporary overvoltage (TOV) caused by the non-islanding operation of distributed generation (DG). Although effective grounding is applied, the TOV can still exceed the allowable voltage defined by the effective grounding. However, previous works did not represent the main contribution of the TOV. Therefore, this study analyzes the characteristics of TOVs caused by the non-islanding operation of DG in an effectively grounded distribution system. Then, it analyzes whether the TOVs can be mitigated by applying a neutral grounding resistor (NGR), which is a practical approach in terms of utility. Consequently, a methodology to calculate the TOVs is introduced. Based on the methodology, the characteristics of total TOVs caused by transformer type, DG type, and DG location were analyzed during the non-islanding operation of DG in an effectively grounded distribution system. Finally, it investigates whether the total TOVs can be lowered by applying an NGR. Thus, this study can provide effective guidelines to determine and mitigate the TOVs caused by the non-islanding operation of DG, enabling the reliable operation of distribution systems with DG.
Keywords: Distributed generation location; Distribution systems; Generation types; Grounding resistor; Interconnection transformer; Islanding operations; Neutral grounding; Neutral grounding resistor; Temporary overvoltages; Transformer types; DG location; Distributed generation; Interconnection transformer; Neutral grounding resistor; Temporary overvoltage